Rural areas of the EU and the influence of globalization on the youth unemployment issue - Pkhakadze, Tamar (Technium Social Sciences Journal, 2021)
To speak about the framework of youth unemployment, there is a strong correlation between the economic performance of the state, the general unemployment rate, and the youth unemployment rate. Most important for the states to improve statistics are to work on economic performance and create better possibilities for the young population of society. The growing economic environment will have a positive effect on the unemployment rate in the short run, but it still tends to be the most important issue of states. Besides, policies might concentrate on developing the areas that will bring into the scale a high potential of employment growth. As an example, we can bring the area of tourism, social services, environmental management, etc. which will be more attractive to young people and will have more potential to get employed. It is obvious, that to develop in the framework of unemployment and especially to concentrate on the youth generation of society, the country needs a full package of economic developments. Youth unemployment is directly linked to the general and broader development stages of the state. Another issue that we have not tackled so far is the unemployment of youth in rural areas.